LINGUISTIС АND SEMАNTIС DIFFERENСES ОF UZBEK АND ENGLISH PRОPER NОUNS (Modern education and development, 2025)
This article explores the linguistic and semantic characteristics of proper nouns (PNs) in English and Uzbek, highlighting their classification, formation, and functional significance. Proper nouns serve as unique identifiers for individuals, places, organizations, historical events, and various entities, reflecting cultural and societal values. The study examines the grammatical and semantic properties of PNs, their morphological structures, and their role in phraseological units. Additionally, the research compares naming conventions in both languages, shedding light on similarities and differences in their linguistic treatment. The findings contribute to a deeper understanding of the function and usage of proper nouns across languages.